Gingival Papilla Dimensions in Anterosuperior Regions Adjacent to Single-Tooth Implants - Perez, Fabiano [UNESP]; Martins Segalla, Jose Claudio [UNESP]; Marcantonio, Elcio [UNESP]; Pereira Lauris, Jose Roberto; Rabelo Ribeiro, Joao Gustavo [UNESP]; Carvalho Ferreira, Luciano Pedrin [UNESP] (Quintessence Publishing Co Inc, 2012)
This study compared the dimensions of gingival papillae in anterosuperior areas presenting at natural teeth (teeth sites) or single-tooth implants adjacent to natural teeth (implant-tooth sites) by analyzing determined distances. A total of 45 teeth and 46 implant-tooth sites were carefully selected. Clinical evaluation consisted of visual and quantitative analyses with millimeter grids on radiographs. Implant-tooth sites showed a smaller gingival papilla dimension than tooth sites (P < .01). Both evaluated distances (contact point to bone crest and between the roots of adjacent teeth or implant platform to root of adjacent tooth) in all groups significantly influenced the presence/absence of gingival papillae (P < .01). (Int J Periodontics Restorative Dent 2012;32:93-100.)